MANFAAT INTERNET MARKETING DALAM MENINGKATKAN PENDAPATAN UMKM PUREE MANGGA (Studi Kasus pada CV. Promindo Utama di Kecamatan Losari, Kabupaten Cirebon) - Rahyan Arfi Mubarak; Lies Sulistyowati (Universitas Galuh, 2020)
Use of the internet for small and medium enterprises (MSMEs) business activities is relatively low, MSME needs to be aware that the development of internet technology has provided efficiency and effectiveness of MSME businesses. One of MSMEs that uses and utilizes the internet as a marketing tool is CV Promindo Utama MSME located in Losari Village, Cirebon Regency. The purpose of this study was to describe how far the internet is used, identify the obstacles faced in using internet marketing and analyze the benefits of internet marketing to increase income and number of consumers of CV Promindo Utama. This study used descriptive qualitative method. The object of this research was CV Promindo Utama, which has used internet marketing as a marketing tool. Data was collected by interview technique. The data was analyzed using Profit analysis Single program before-after method. The results of this study indicates that CV Promindo Utama has used the internet as a promotional tool to market its products through different web platforms, social media and online shopping, while the obstacles faced in the usage of internet marketing by CV Promindo Utama was the lack of related knowledge regarding the internet used, lack of workforce who are experts in the field of technology and inadequate signals, with use of internet marketing many benefits were obtained in increasing revenue and increasing number of consumers so that MSME CV Promindo Utama can develop and expand sales market, where the monthly profit increased by 13,7% and the number of consumers were increased by 25% per month after the usage of internet marketing.